ナンキョク VICTORIA LAND ノ DRY VALLEY チョウサ ホウコク 1. ナンキョク VICTORIA LAND ノ MIERS VALLEY ニ サン スル EVAPORITE ニツイテ - 鳥居, 鉄也; トリイ, テツヤ; 村田, 貞雄; ムラタ, サダオ; 吉田, 栄夫; ヨシダ, ヨシオ; 小坂, 丈予; オサカ, ジョウヨ; 山県, 登; ヤマガタ, ノボル; TORII, Tetsuya; MURATA, Sadao; et al. (国立極地研究所, 1966)
P(論文) Reconnaissance of Lake Miers in the Dry Valley region, Victoria Land was made by a summer party supported by the U. S. National Science Foundation This report summarizes the description of occurrence and characteristics of the crystalline salt deposits found on and beneath the morains on the bottom of the Miers Valley, in this report these deposits are called "evapontes" although the mechanism of the formation of these deposits is still obscure. The mam characteristics of the climate in the Dry Valley are quite arid condition and comparatively high temperatures in summer and strong wind, which are considered to be ascribed chiefly to the low albedo of widely exposed rocks to the insolation in summer and the compressional effect (pseudofoehn phenomenon) of katabatic wind. These circumstances may have a close relation to the mechanism of formation of the evapontes. The Miers Valley was once covered with glaciers and by the retreat of the glaciers the U-shaped valley was formed, the floor of which being widely covered with moraines. The moraines are composed of undifferentiated material of the Koettlitz Glacier origin, which was grouped into four types by BLANK. The moraines are quite flat in part, suggesting a levelling action of water (lake water?). Patterned ground is commonly developed in the moraines Lake Miers is located at the bottom of the valley and ill-defined old strand lines of the lake can be observed The lake water is not saline probably because of the presence of an outlet stream. The evaporites can be grouped into three types by the mode of occurrence (1) platelike aggregates of crystals spread over the flat moraines (Sample Nos. 65M60, 65M80, 65M90, 65M1001, 65M1002, Photo 3), (2) cloddy crystal aggregates on the ridge of moraines, some of which lie directly on the core of ice (Sample Nos 65M30, 65M402, 65M401, Photo. 4) and, (3) horizontal layers interbedded with moraines, exposed on the flank of a gorge which was formed by downcutting of an outlet stream (Sample Nos 65M501, 65M502, ...